Bibliometric Analysis of Information Technology Learning Media Research with Vosviewer - patty, Elyakim Nova Supriyedi; Marlina; Heri Sopian Hadi; Abdul Rahim (LPPM Institut Studi Islam Sunan Doe, 2024)
The aim of this study is to systematically analyze and demonstrate a step-by-step bibliometric analysis of data with VOSViewer. It can be concluded that the topic of information technology learning media can be integrated with other learning fields. This study presents data analysis related to the study of information technology learning media and its development over the last fifteen years (2009-2023) using the mapping tool in VOSViewer. Bibliometric analysis performance by creating web visualization of selected topics using descriptive qualitative methods. From the search results, 996 relevant journals were found published from 2009 to 2023, which were then divided into 15 categories based on the year of publication. After sifting through journal data, we found that the highest number of articles were published in 2017-2021, with a peak in 2020. There are many opportunities to discover new things about this topic. So this research will be an inspiration for writers who conduct research and determine research topics.